Coping Strategies Adopted By First Year Medical Students and Their Academic Outcomes: Life Sciences-Medical - Jaiganesh, K; Sobana, R; Bharathi, P (International Journal of Life Science and Pharma Research, 2022)
Medical students tend to experience greater overall psychological distress when compared to the levels of distress observed in the general population. A careful analysis of the coping behaviors and their associations with personality factors etc., in the light of their biological basis, may offer important clues for successful interventions in order to yield fruitful academic outcomes. The fundamental aim was to evaluate the associations between the choice of coping strategies and the Big Five Personality traits among academic high- and low-achievers, and average students who have recently been exposed to the medical curriculum. The other three aims were to evaluate the relationship between the employment of coping strategies and psych morbidity among the above group; to explore the gender-based differences among the above student category; to assess the variations in the associations of adaptive/maladaptive coping with relationship to personality and other factors in the light of higher biological control mechanisms. The voluntary participants of the study include one hundred and forty-two first year medical students (68 males, 74 females) from a private University in Puducherry state, South India. The self-rating anxiety scale and self-rating depression scales were found out. The personality traits were elucidated using the NEO-FFI (NEO Five Factor Inventory), which was administered to all the participants. Those with T-scores above 50 were classified as having elevation in the concerned personality trait. After evaluating the scores of the various personality traits. The average marks secured by the students in four consecutive academic examinations was entered. Correlations between the coping strategies and the above mentioned factors among low- achievers revealed a) a small negative association between TOC and Neuroticism (p<0.05); b) a small positive correlation between EOC and anxiety scores (p<0.05); c) a negative association between TOC and anxiety and depression (p<0.05); and d) a negative association between AOC-SD and depression scores (p<0.05) were noted. . Studies concerning the link between coping strategies, personality and psychopathology may help in identifying certain risk and resilience factors that could influence the impact of stressful academic training for individual students.